2020
DOI: 10.1111/jnc.15242
|View full text |Cite
|
Sign up to set email alerts
|

Mulberroside A repairs high fructose diet‐induced damage of intestinal epithelial and blood–brain barriers in mice: A potential for preventing hippocampal neuroinflammatory injury

Abstract: Our previous studies showed that high fructose diet (HFrD)‐driven gut dysbiosis caused fecal short‐chain fatty acids (SCFAs) reduction and intestinal epithelial barrier (IEB) damage in mice, which might play an important role in hippocampal neuroinflammatory injury. Mulberroside A is reported to have neuroprotective effects in animal experiments, while the underlying mechanisms are not yet fully elucidated. Here, we investigated whether and how mulberroside A prevented HFrD‐induced neuroinflammatory injury. HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Additionally, the sesamolin-treated group showed increases in the abundances of Muribaculaceae , Bacteroidaceae , and Prevotellaceae . Furthermore, the correlation analysis revealed that these harmful bacterial florae were positively correlated with these risk factors involved in intestinal barrier dysfunction, endotoxemia, metabolic disorder, and renal injury, whereas these beneficial bacterial florae display a negative correlation with them, which are consistent with these previous findings. These results suggest that sesamolin treatment attenuates gut microbiota imbalance in HF–HF diet-fed mice, which might be highly correlated with the alleviation of intestinal barrier dysfunction, endotoxemia, metabolic disorder, and renal injury. The improvement of intestinal barrier dysfunction through modulating gut microbiota by sesamolin treatment might contribute to reducing the translocation of bacterial metabolites and endotoxins into blood circulation and thereby suppressing endotoxin-driven pathways and metabolic disorders to protect against the development of renal injury in HF–HF diet-fed mice.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, the sesamolin-treated group showed increases in the abundances of Muribaculaceae , Bacteroidaceae , and Prevotellaceae . Furthermore, the correlation analysis revealed that these harmful bacterial florae were positively correlated with these risk factors involved in intestinal barrier dysfunction, endotoxemia, metabolic disorder, and renal injury, whereas these beneficial bacterial florae display a negative correlation with them, which are consistent with these previous findings. These results suggest that sesamolin treatment attenuates gut microbiota imbalance in HF–HF diet-fed mice, which might be highly correlated with the alleviation of intestinal barrier dysfunction, endotoxemia, metabolic disorder, and renal injury. The improvement of intestinal barrier dysfunction through modulating gut microbiota by sesamolin treatment might contribute to reducing the translocation of bacterial metabolites and endotoxins into blood circulation and thereby suppressing endotoxin-driven pathways and metabolic disorders to protect against the development of renal injury in HF–HF diet-fed mice.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, the gut barrier dysfunction is often considered the main reason for an elevation in serum endotoxin concentrations and translocations of more bacterial metabolites into the systemic circulation . The intestinal barrier consists of multiple layers, and the epithelial cell layer that produces intestinal alkaline phosphatase (IAP) and antibacterial proteins plays a key role in the host defense, which protects against the translocations of more bacterial metabolites and active endotoxins into the systemic circulation. , However, evidence has shown that the ingestion of a high-fat diet or/and a high-fructose diet could cause intestinal epithelial cell damage and an increase in circling bacterial endotoxins, , Additionally, the intestinal epithelial cell damage often accompanies the metabolic disorders in high-fat diet-fed animals. , Notably, in addition to endotoxins, the microbial metabolites have also been found to be in association with the development of obesity and metabolic disorders. , In contrast, sesamolin treatment alleviated intestinal barrier dysfunction along with lowering levels of serum endotoxins and metabolic biomarkers. Therefore, the decrease in circling endotoxins as a result of sesamolin treatment might be linked to its effect on the improvement of intestinal barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all experiments, no blinding was performed. We designed the number of subjects used in this experiment based on the previous studies (Jun et al., 2018; Yu et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Mulberroside A, presenting at relatively high abundance in the roots and twigs of Morus alba L. ( Zhou et al, 2013 ), is a natural polyhydroxylated stilbene compound ( Yu et al, 2021 ). Furthermore, it possesses various therapeutic effects through pharmacological studies, including hypoglycemic ( Li et al, 2014 ), antidiabetic ( Xu et al, 2021 ), anti-inflammatory ( Chung et al, 2003 ), analgesic ( Zhang and Shi, 2010 ), hepatic protective function ( Zhang et al, 2008 ), nephroprotective ( Wang et al, 2011 ), the inhibitory effect of melanogenesis ( Park et al, 2011 ) and neuroprotective ( Wang C. P. et al, 2014 ) effects, etc.…”
Section: Introductionmentioning
confidence: 99%